Weekend versus weekday transplant surgery and outcomes after kidney transplantation in the USA: a retrospective national database analysis. Issue 4 (7th April 2016) - Baid-Agrawal, Seema; Martus, Peter; Feldman, Harold; Kramer, Holly
Abstract : Objective: To determine whether kidney transplants performed during a weekend had worse outcomes than those performed during weekdays. Design: Retrospective national database study. Setting: United Network for Organ Sharing database of the USA. Participants: 136 715 adult recipients of deceased donor single organ kidney transplants in the USA between 4/1994 and 9/2010. Main outcome measures: The primary outcomes were patient survival and death-censored and overall allograft survival. Secondary outcomes included initial length of hospital stay after transplantation, delayed allograft function, acute rejection within the first year of transplant, and patient and allograft survival at 1 month and at 1 year after transplantation. Cox proportional hazards models were used to evaluate the impact of weekend kidney transplant surgery on primary and secondary outcomes, adjusting for multiple covariates. Results: Among the 136 715 kidney recipients, 72.5% underwent transplantation during a regular weekday (Monday–Friday) and 27.5% during a weekend (Saturday–Sunday). No significant association was noted between weekend transplant status and patient survival, death-censored allograft survival or overall allograft survival in the adjusted analyses (HR 1.01 (95% CI 0.92 to 1.04), 1.012 (95% CI 0.99 to 1.034), 1.012 (95% CI 0.984 to 1.04), respectively). In addition, no significant association was noted between weekend transplant status and the secondary outcomes of patient and graft survival at 1 month and 1 year, delayed allograft function or acute rejection within the first year. Results remained consistent across all definitions of weekend status. Conclusions: The outcomes for deceased donor kidney transplantation in the USA are not affected by the day of surgery. The operationalisation of deceased donor kidney transplantation may provide a model for other surgeries or emergency procedures that occur over the weekend, and may help reduce length of hospital stay and improve outcomes.